Micropropagation, encapsulation, physiological, and genetic homogeneity assessment in Casuarina equisetifolia - Ahmad, Zishan; Yadav, Vikas; Shahzad, Anwar; Emamverdian, Abolghassem; Ramakrishnan, Muthusamy; Ding, Yulong (Frontiers in Plant Science, 2022)
Casurina equisetifolia is an important tree of forest cultivated in tropical and subtropical regions, providing fuelwood, land reclamation, dune stabilization, paper production and nitrogen fixation. We have developed a systematic in vitro propagation protocol in C. equisetifolia using nodal segments (NS). Murashige and Skoog (MS) medium augmented with BA (5.0 M) and NAA (0.5 M) gave rise to a maximum of 32.00 ± 0.31 shoots per explant (S/E) with shoot length (SL) of 3.94 ± 0.02 cm and a maximum of 70% regeneration potential (RP) was recorded after 8 weeks of post inoculation. For root induction, in vitro derived shoots were transferred to the nutrient medium consisting of half-strength (½) MS medium augmented with 2.5 μM NAA, which produced a maximum of 12.68 ± 0.33 roots/shoot (R/S) with 3.04 ± 0.50 cm root length (RL) in 60% of culture after 6 weeks. Micropropagated plants with healthy shoots and roots were successfully acclimatized in vermicompost + garden soil + sand (1:2:1) and a maximum survival percentage of 95.1 % was recorded. NS taken from 6 weeks old in vitro derived plant of C. equisetifolia for synthetic seed production and it was reported that CaCl2∙2H2O (100 mM) + Na2-alginate (4%) resulted in clear and uniform beads. Furthermore, the maximum conversion of synthetic seeds into plantlets occurred over a period of 4 weeks of storage at 4 ºC. Scanning Electron Microscopy (SEM) revealed the formation of direct shoot buds without any intermediate callus formation. In addition, the chlorophyll and carotenoid content of the direct regenerated and mother plant were compared. Similarly, RAPD and ISSR primers were used for genetic homogeneity assessment of direct regenerated plant, where a total of 18 and 19, respectively, clear and reproducible bands with100% monomorphism were recorded. The developed micropropagation protocol can certainly be used for large-scale multiplication and germplasm preservation of C. equisetifolia. It will also help in meeting the growing demands of C. equisetifolia in the forest industry.